Pertumbuhan dan Produksi Dioscorea sansibarensis Pax pada Perlakuan Panjang lanjaran dan Waktu Batang Membelit* - ,, solikin (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
Dioscorea is potentially used as staple food to support food security. The research was aimed to determine the effect of stake length and time of  stem twining  on  the growth of Dioscorea sansibarensis Pax. The experiment was conducted  in  Purwodadi Botanic Garden from December 2014 until May 2015 using split plot randomized block design consisted of two factors, i.e. the stake length and time of stem twining. The stake length was the main plot consisted of 150 cm, 100 cm and 50 cm above soil surface and without stake (control). The time of stem twining as subplots, i.e. stem twined early, twined at the time of 4 leaves stage, and twined at 8 leaves stage. Each combination of the treatments was replicated three times. The results showed that there was significant effect on the stake length  and the time of stem twining treatments on the plant growth and yield. The stake  length of 150 cm treatment produced the highest fresh tuber and total plant dry weight, i.e., 257.24 g and 132.77 g per plant, respectively. On the contrary, the plant without stake produced the lowest fresh tuber and  total dry weight of plant, i.e., 112.10 g and 48.65 g per plant, respectively.Keywords: biomass,leaf area, photosyntesis, tuber weight